Anastomotic Recurrence of Sigmoid Colon Cancer over Five Years after Surgery - Yamauchi, Takahiro (S. Karger AG, 2013)
The incidence of anastomotic recurrence after curative resection of colorectal cancer is relatively low compared to that of other types of recurrence, such as hepatic, lung and local recurrence. However, almost all cases of anastomotic recurrence of colorectal cancer occur within 3 years after surgery. We experienced a rare case of anastomotic recurrence in whom colonoscopy revealed no signs of recurrence 3 years after surgery; however, anastomotic recurrence was detected over 5 years after surgery. A 60-year-old female with a history of surgery for cancer of the cecum in her forties underwent sigmoidectomy and right colectomy with D3 lymph node dissection for both stage IIA sigmoid colon cancer and stage IIA transverse colon cancer. Computed tomography and colonoscopy revealed no signs of recurrence 3 years after surgery; however, 5 years and 4 months after surgery, colonoscopy demonstrated surrounding flaring and swelling in the anastomotic area of the sigmoid colon, and a biopsy revealed an adenocarcinoma. Under the diagnosis of anastomotic recurrence over 5 years after surgery, lower anterior resection was performed. The patient has exhibited no other signs of recurrence in the 2 years since the last operation.